Non-canonical retinoid signaling in neural development, regeneration and synaptic function - Piazza, Alicia; Carlone, Robert; Spencer, Gaynor E. (Frontiers in Molecular Neuroscience, 2024)
Canonical retinoid signaling via nuclear receptors and gene regulation is critical for the initiation of developmental processes such as cellular differentiation, patterning and neurite outgrowth, but also mediates nerve regeneration and synaptic functions in adult nervous systems. In addition to canonical transcriptional regulation, retinoids also exert rapid effects, and there are now multiple lines of evidence supporting non-canonical retinoid actions outside of the nucleus, including in dendrites and axons. Together, canonical and non-canonical retinoid signaling provide the precise temporal and spatial control necessary to achieve the fine cellular coordination required for proper nervous system function. Here, we examine and discuss the evidence supporting non-canonical actions of retinoids in neural development and regeneration as well as synaptic function, including a review of the proposed molecular mechanisms involved.